What color is the sacred? - Taussig, Michael T. (The University of Chicago Press, 2009)
Over the past thirty years, visionary anthropologist Michael Taussig has crafted a highly distinctive body of work. Playful, enthralling, and whip-smart, his writing makes ingenious connections between ideas, thinkers, and things. An extended meditation on the mysteries of color and the fascination they provoke, What Color Is the Sacred? is the next step on Taussig’s remarkable intellectual path.